Defining attributes of patient safety through a concept analysis. (30th June 2015) - Kim, Linda; Lyder, Courtney H.; McNeese‐Smith, Donna; Leach, Linda Searle; Needleman, Jack
Abstract Aim The aim of this study was to report an analysis of the concept of patient safety. Background Despite recent increase in the number of work being done to clarify the concept and standardize measurement of patient safety, there are still huge variations in how the term is conceptualized and how to measure patient safety data across various healthcare settings and in research. Design Concept analysis. Data sources A literature search was conducted through PubMed and Cumulative Index to Nursing and Allied Health Literature, Plus using the terms 'patient safety' in the title and 'concept analysis, ' 'attributes' or 'definition' in the title and or abstract. All English language literature published between 2002–2014 were considered for the review. Methods Walker and Avant's method guided this analysis. Results The defining attributes of patient safety include prevention of medical errors and avoidable adverse events, protection of patients from harm or injury and collaborative efforts by individual healthcare providers and a strong, well‐integrated healthcare system. The application of Collaborative Alliance of Nursing Outcomes indicators as empirical referents would facilitate the measurement of patient safety. Conclusion With the knowledge gained from this analysis, nurses may improve patient surveillance efforts that identify potential hazards before they become adverse events and have a stronger voice in health policy decision‐making that influence implementation efforts aimed at promoting patient safety, worldwide. Further studies are needed on development of a conceptual model and framework that can aid with collection and measurement of standardized patient safety data.